Tazkiya al-Nafs as a Moral Education in Libyan Universities: Student Attitudes toward Spiritual Practices in Islamic Studies and Sharia Programs - Naser Abdulghani; Nahid Ayad; Mohieddin Masoud; Sami Barkah; Salem Aladi; Abdulghani Abouzied (Cigarskruie: Journal of Educational and Islamic Research, 2025)
This study examines attitudes toward tazkiyah al-nafs as a form of moral education and the acceptability of spiritually related practices within Libyan higher education. To contextualise and explain survey patterns, semi-structured interviews were conducted with 25 lecturers. Quantitative results indicated strong endorsement of tazkiyah as a basis for character formation and self-control, accompanied by moderate perceptions of feasibility and a concern regarding labelling, with students preferring tazkiyah/akhlaq framing over explicitly “Sufi” labelling. The acceptability results revealed a clear incline. Acceptability results revealed a clear inclination toward educationally framed practices (intention-setting, guided reflection, virtues application, and adab-related service). Conversely, practices likely to be interpreted as public ritual or identity-marked activity (collective loud dhikr, zawiya visits) were viewed as sensitive. Interview findings suggested that acceptance is contingent upon clarity of education, voluntariness, and avoidance of contested symbolism. The study concludes that tazkiyah al-nafs, as an institutionally neutral model, offers a practical pathway for moral education within Libyan university contexts.